Surveying the Effect of Hydroalcoholic Extract of Allium hirtifolium on Glycated Hemoglobin Formation in In-vitro Condition - Shirin Fattahpour; Farzaneh Hosseini; Mohammad Reza Hajizadeh; Mohammad Asadpour; gholam hossein hassanshahi; mohammad reza mirzaii; Mehdi Mahmoodi (Fasa University of Medical Sciences, 2015)
Background & Objectives: Non enzymatic glycation is a reaction that occurs between reducing sugars and amino groups of proteins. Advanced Glycation End-products (AGE) have been accounted for principal biological processes like aging and pathogenesis of some diseases. Accumulation of AGE during hyperglycemia can cause structural and functional changes of long-lived proteins. Therefore, it will be effective to inhibit protein glycation formation in order to reduce or to improve diabetes complications. The aim of this study is to determine the effects of hydroalcoholic extract of Allium Hirtifolium on the formation of glycated hemoglobin.    Materials & Methods: In this experimental study, the effects of the various concentrations of 0.1, 0.3, and 0.5 gr/dl of hydroalcoholic extract of Allium Hirtifolium on the inhibition of hemoglobin glycation were examined. Hemoglobin A1c formation was assayed by ion exchange chromatography. The P-value < 0.05 was considered as the significant level.    Results: 10 and 14 days after incubation, at the concentration of 40 millimollar glucose, hemoglobin A1c formation decreased significantly by using 0.5 gr/dl of hydroalcoholic extract of Allium Hirtifolium.    Conclusion: The results revealed that Allium Hirtifolium can inhibit hemoglobin A1c formation in hyperglycemic condition. Therefore, it is suggested that Allium Hirtifolium can be useful for preventing the complications of diabetes.